Implementasi Aplikasi Toy App dan Modul Ajar Berbasis Proyek di SD Negeri 1 Padenganploso Kabupaten Lamongan - Wahyu Kyestiati Sumarno; Ali Shodikin; Nur Imro’atus Solikha; Novandi Kevin Pratama (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Digital literacy is one of the most needed 21st century skills. The effectiveness of integrating the use of technology in project-based learning has proven to be effective in increasing digital literacy skills. Toy App is an Android-based application designed as a medium for learning basic literacy and numeracy. The purpose of this community service activity is to implement the Toy App application and project-based teaching modules to increase digital literacy in students. This activity was carried out for students at SD Negeri 1 Padenganploso, Pucuk District, Lamongan Regency. The results of this activity show that the implementation of the Toy App and project-based teaching modules has a positive impact on increasing digital literacy in students. In addition, the learning process is also more fun. Based on these results, the application of the Toy App application and project-based teaching modules can be used as an alternative in supporting digital literacy in elementary school students.